The shear lag effect of composite box girder bridges with corrugated steel webs. (February 2023) - Jiang, Ruijuan; Wu, Qiming; Xiao, Yufeng; Peng, Manlin; Tat Kwong Au, Francis; Xu, Tianhua; Chen, Xiachun
Abstract: The composite box girder bridge with corrugated steel webs has been constructed throughout the world since its debut in France in 1986 due to its various advantages. Since the shear lag effect is very essential to the safety of this kind of structure and it is seldom issued, in this paper a theoretical method is firstly developed based on the energy variational principle and then a finite difference solution procedure for the analysis of the shear lag effect of this kind of bridge. Afterwards, a new definition of effective flange width applicable to thickness-varying flanges is proposed. This new definition is then adopted to obtain the effective flange width coefficient that can indicate the characteristics of the shear lag effect. To validate the proposed semi-analytical method and to investigate the characteristics of shear lag effect, the semi-analytical method and finite element method are used to estimate the effective flange width coefficient of simply-supported and continuous bridges of this kind. The comparison of the two methods shows that the semi-analytical method can accurately predict the effective flange width coefficient. Under uniformly distributed loading, positive shear lag effect can be observed throughout the whole bridge when it is simply supported. For continuous bridges under uniformly distributed loading, the magnitude of shear lag effect in each span reduces with the increase of the effective span length. Finally, the applicability of technical provisions about effective flange width in design codes is studied, and some design suggestions are proposed for the effective flange width and the shear lag effect of this kind of bridge based on a comprehensive parametric study that is carried out using the semi-analytical method.